Knee flexor and extensor isoknetic strength profles of elite male golfers - GERÇEK, NEJLA; TATAR, YAŞAR (My University, 2022)
Objectve: Although lower extremity plays an important role for postural control and to produce power during the golf swing, it has not been clearly examined. The aim of this study was to identify the left-right, and agonist-antagonist knee muscle strength profiles and its correlation with performan‐ ce in proficient golfers. Materals and Methods: Eight male elite golfers, age 21.6±1.1 years, height 174.1±6.1 cm, and body mass 68.6±2.7 kg, with handicaps of 0-5 parti‐ cipated in the study. Knee flexor and extensor peak torques of the golfers were measured by using isokinetic dynamometer (at 60°/s, 120°/s and 240°/s). The number of golf shots on an 18-hole golf course was recorded to determine golf performance. Results: In golf players, knee strength difference between right and left extremities were 0.53%, 5.77% and 5.35% for flexor muscles and 5.71%, 3.60% and 7.91% for extensor muscles at 60°/s, 120°/s and 180°/s, respectively. Right and left knee Fcon/Excon ratio was between 0.67-0.99. No correlation was found between golf performance and peak torques except for right knee flexor muscle at 120°/s angular velocity. Conclusons: Knee muscle strength variations between right-left and agonist-antagonist muscles were below the injury risk limits. Those negligible im‐ balances may be the result of functional differences of knee muscles during each part of the golf swing. It is important to add appropriate drills to the training programs so that these differences do not cause injury and poor performance in the long term.

Amaç: Alt ekstremite, golf vuruşu sırasında postüral kontrol ve güç üretmek için önemli bir rol oynamasına karşın, detaylı olarak incelenmemiştir. Bu ça‐ lışmanın amacı, elit golfçülerde sol-sağ ve agonist-antagonist diz kas kuvvet profillerini ve performans ile ilişkisini belirlemektir. Gereç ve Yöntem: Çalışmaya yaşları 21.6±1.1 yıl, boyları 174.0±6.1 cm ve vücut ağırlıkları 68.6±2.7 kg olan 0-5 handikaplı sekiz erkek elit golfçü katıl‐ dı. Golfçülerin diz fleksör ve ekstansör zirve torkları izokinetik dinamometre (60°/s, 120°/s ve 240°/s) kullanılarak ölçüldü. Golf performansı, 18 delikli bir golf sahasındaki golf atışlarının sayısı kaydedilerek değerlendirildi. Bulgular: Golf oyuncularında sağ ve sol ekstremiteler arasındaki diz kuvveti farkı 60°/s, 120°/s ve 180°/s açısal hızlarda sırasıyla fleksör kaslar için %0.53, %5.77 ve %5.35; ekstansör kaslar için %5.71, %3.60 ve %7.91 olarak bulundu. Sağ ve sol diz Fcon/Excon oranı 0.67-0.99 arasındaydı. Golf performansı ile zirve torkları arasında, 120°/s açısal hızdaki sağ diz fleksör kası dışında, bir ilişki bulunmadı. Sonuç: Sağ-sol ve agonist-antagonist kaslar arasındaki diz kas kuvveti farkları yaralanma risk limitlerinin altındaydı. Bu göz ardı edilebilir dengesizlikler, golf vuruşunun her bir bölümünde diz kaslarının fonksiyonel farklılıklarının sonucu olabilir. Bu farklılıkların uzun vadede yaralanmalara ve performans dü‐ şüklüğüne neden olmaması için antrenman programlarına gerekli egzersizlerin eklenmesi önemlidir.
Keywords: Golf; knee strength; strength ratio; lower extremity; diz kuvveti; kuvvet oranı; alt ekstremite